RESEARCH OF THE INFLUENCE OF THE MOVEMENT MECHANISM ON THE RESOURCE OF METAL STRUCTURES OF OVERHEAD CRANES OF SEAPORTS - STRELBITSKIY, Victor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Overhead cranes are widely used when performing reloading operations on closed ones (fig.1) and open warehouses of sea and river ports. Since they are a link in the technological process, the productivity of Port lines depends on their reliable and continuous operation. Overtime and long term operation of metal structures of overhead cranes in the mode of intensive cyclic loading leads to the formation of fatigue defects and subsequent failure of components and accidents. The main criterion for achieving the maximum condition of metal structures is considered to be the development of its resource, and their technical diagnostics and expert examination remain the method of establishing the real condition of cranes. The paper presents the results of studies of overhead cranes that are operated in closed warehouses of seaports. The 8 bridge cranes of the same type were selected for research, with a load capacity of 10 tons, which are made of ВСтЗсп5 steel, operate in Hook mode and operate in closed warehouses of ports. The crane travel path did not exceed 24 m. To assess the stress-strain state of metal structures of end beams, the method of magnetic (coercimetric) monitoring using a КРМ-Ц-К2М magnetic structuroscope was used. The measurements were carried out over three years, with a frequency of 1 time per year. On the metal structure of the crane, it was necessary to select the area where the force effect on the metal was the least during operation, and the values of the coercive force (a/CM) were measured. The obtained values are comparable to the passport values, the difference did not exceed 10%.. Experimentally, it was found that the most loaded node of the overhead crane is the end beams, since they have the greatest amount of damage. It was found that the greatest stresses occur in the attachment point of the corner axle boxes of the running wheels on the end beams, which are affected by vertical loads and transverse horizontal forces that occur when the crane moves. Two cranes have been found to have emergency cracks, so they need to be repaired or replaced. To obtain objective information, it is necessary to periodically monitor and regularly enter the NS value in the work log, while noting the actual values and intensity of the load.